Recent Publications (Quarterly Journal of Economics, 1938)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 53, Issue 1, November 1938, Pages 161–165, https://doi.org/10.1093/qje/53.1.161 Published: 01 November 1938